2020
DOI: 10.3390/ma13112619
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent Pore Channel Model for Fluid Flow in Rock Based on Microscale X-ray CT Imaging

Abstract: Pore-scale modeling with a reconstructed rock microstructure has become a dominant technique for fluid flow characterization in rock thanks to technological improvements in X-ray computed tomography (CT) imaging. A new method for the construction of a pore channel model from micro-CT image analysis is suggested to improve computational efficiency by simplifying a highly complex pore structure. Ternary segmentation was applied through matching a pore volume experimentally measured by mercury intrusion porosimet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 47 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…3 (d), the simplification principle is to reduce the connection points to make the curve smooth, to obtain the orifice image Fig. 3 (e) [ 37 ]. Fig.…”
Section: Methodsmentioning
confidence: 99%
“…3 (d), the simplification principle is to reduce the connection points to make the curve smooth, to obtain the orifice image Fig. 3 (e) [ 37 ]. Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In such cases, the local permeability is described by Hagen‐Poiseuille law, k=di2ϕ64 $k=\frac{{d}_{i}^{2}\phi }{64}$. The microtube diameter value is constrained by correlating the pore‐size distribution obtained experimentally using mercury injection capillary pressure with the mapping of the local porosity field in the unresolved region (Choi et al., 2020; Yang, Kang, & Yun, 2021). Even though further work still needs to be done to reconstruct accurately the unresolved pores using the pore‐size distribution and the grayscale images, micro‐continuum models have demonstrated their abilities to compute absolute permeability including the instrument resolution.…”
Section: Applications In Geosciencesmentioning
confidence: 99%
“…The study suggested that HC of peat soils was greatly regulated by a pore shape coefficient which was generally supposed to contain pore characteristics like PSD, path tortuosity, roundness, and sphericity of pores. A pore channel model developed with different pore segments showed that flow in water varied with the pore shape in 2D images whereas tortuosity is prominent in 3D images (Choi et al, 2020). For the characterization of all the factors required for pore geometry, X-ray micro-CT equipment was used with a voxel size ranging from 3 to 10 μm and commercial Avizo software was used to visualize, and analyse the stacked image.…”
Section: Water Content and Solute Transportmentioning
confidence: 99%